EUROPEAN UNION-UKRAINE AGRICULTURAL TRADE DURING THE RUSSO-UKRAINIAN WAR: A POLITICAL ECONOMY PERSPECTIVE - Aldona Zawojska; Tomasz Siudek (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2024)
The article analyzes the consequences of the Russian armed invasion of Ukraine, initiated in February 2022, for the EU’s trade policy towards this country and for the changes in mutual foreign trade in agri-food goods due to its temporary, exceptional liberalization, with particular emphasis on the imports of these products into the EU. The study uses the political economy approach (including interest group theory) to explain the premises of the EU’s specific trade policy towards Ukraine and the crisis in mutual trade relations between Ukraine and its neighboring countries, caused by the excessive inflow of Ukrainian grain into their territories. Large agri-food corporations are identified as potential interest groups monopolizing economic power, influencing the use of agricultural land, the export of agricultural products, and Ukraine’s domestic and foreign policy. The measures of temporary liberalization of trade in agricultural products applied by the EU to Ukraine in response to the war situation resulted in a significant increase in their imports into the EU, while in the case of Poland its share in the volume of EU imports of sensitive products (wheat, maize, rapeseed and sunflower) in the 14 months since the beginning of the war was several to over a dozen times higher than in the 11 months preceding Russia’s invasion of Ukraine.